222k views
8 votes
The arithmetic-geometric mean (AM-GM) inequality: if a,b ≥ 0, then
(a+b)/(2) \geq √(ab). (1)

(a) Let a, b, c, d ≥ 0 and consider the positive real numbers
√(ab) and
√(cd). Use (1) to prove the four-variable AM-GM inequality:


(a+b+c+d)/(4) \geq \sqrt[4]{abcd}. (2)

(b) Let a, b, c ≥ 0 and define
m= (a+b+c)/(3).

(i) Show that
m=(a+b+c+m)/(4).

(ii) Hence use (2) to prove the three-variable AM-GM inequality:


(a+b+c)/(3) \geq \sqrt[3]{abc}.

1 Answer

3 votes

(a) The inequality follows from the binomial theorem.


(a - b)^2 = a^2 - 2ab + b^2 \ge 0 \implies a^2 + 2ab + b^2 = (a+b)^2 \ge 4ab \\\\ \implies \frac{(a+b)^2}4 \ge ab \\\\ \implies \frac{a+b}2 \ge √(ab) ~~~~~~~~ (1)

By the same reasoning,


\frac{c+d}2 \ge √(cd)

Adding these results together, we have


\frac{a+b}2 + \frac{c+d}2 = \frac{a+b+c+d}2 \ge √(ab) + √(cd)

and since
√(ab) and
√(cd) are both positive, they also satisfy the AM-GM inequality,


\frac{√(ab) + √(cd)}2 \ge \sqrt{√(ab)*√(cd)} = \sqrt[4]{abcd}

and the 4-variable result follows,


\frac{a+b+c+d}2 \ge 2*\frac{√(ab)+√(cd)}2 \ge 2 \sqrt[4]{abcd} \\\\ \implies \frac{a+b+c+d}4 \ge \sqrt[4]{abcd} ~~~~~~~~ (2)

(b.i) With
m=\frac{a+b+c}3, we have


\frac{3m}4 = \frac{a+b+c}4 \implies m - \frac m4 = \frac{a+b+c}4 \\\\ \implies m = \frac{a+b+c+m}4

(b.ii) From (2) it follows that


\frac{a+b+c+m}4 \ge \sqrt[4]{abcm} = \sqrt[4]{abc*\frac{a+b+c+m}4}

Using the result from (b.i), this is equivalent to


\frac{a+b+c}3 \ge \sqrt[4]{abc*\frac{a+b+c}3}

Take 4th powers on both sides.


\left(\frac{a+b+c}3\right)^4 \ge abc * \frac{a+b+c}3

Divide both sides by
\frac{a+b+c}3.


\left(\frac{a+b+c}3\right)^3 \ge abc

Finally, take the cube root of both sides.


\frac{a+b+c}3 \ge \sqrt[3]{abc}

as required.

User Denten
by
5.9k points